Synthesis and Characterization of Some New 1,2,3-Triazole, Amic Acids, Imides, and Isoimides from Ethyl-p-aminobenzoate and -Study Their Biological Activity - Al-Majidi, Suaad M H; Saeed, Zahraa Sabah (Al-Nahrain Journal of Science, 2013)
This research includes the synthesis new series of hetrocyclic compounds by three routes. The first route include synthesis of N-ethylbenzoate-1,2,3-triazole derives (3,4) by diazotation of ethyl-p-amino benzoate and treating the resulted salt (1) with sodium azid, then ethyl acetoacetate or acetyl acetone, respectively. The second route, ethyl-p-aminobenzoate was allowed to react with five of acid anhydrides (maleic, phthalic, cis-1,2,3,4-tetrahydro phthalic, succinic and glutaric) produced five novel esters contain amic acids (5-9), the third route include conversion these esters contain amic acids (5-9). The third route include conversation these esters amic acids (5-9) to different isoimides (10-14) and imide (15-19) respectively, through by two different methods. The first method treatment the amic acids (5-9) was dehydrated using strong dehydrating agents. N,N-dicyclohexyl carbodiimide (DCC) or trifloroacetic anhydride-triethylamine, we obtained the isoimide (10-14). While the second method involved direct reaction of amic acids (5-9) with a mixture of acetic anhydride and anhydrous sodium acetate to give cyclic imide (15-19). The prepared compounds identified by spectral methods [FTIR, 1H-NMR, 13C-NMR] and measurement some of its physical properties. Furthermore antibacterial activity of some the prepared new cyclic compounds were evaluated against three types of bacteria.